Proteomics approaches in identification of key signalling pathways associated with collagen type 1-induced osteogenic differentiation of dental stem cells - Nasir, Nur Julia Nabila (2024)
Collagen type 1 (Col-1) is a promising scaffolding material in bone regeneration approach. However, the predominant signalling pathway involved when dental pulp stem cells (DPSC) cultured on the scaffold are still poorly understood. This study analysed the stemness of the DPSC prior to the studies of relevant signalling pathways involved and the proteomic profiles to determine the mechanism underlying the Col-1 induced osteogenesis. Characterisation of DPSC were analysed via its morphology, MSC surface markers, population doubling level as well as differentiation capacity. For the signalling pathways analysis, cells were grouped into complete culture medium (CCM; negative control), osteogenic induction medium (OIM; positive control) and Col-1 without and with three different pathway inhibitors: LY294002 (PI3K/AKT inhibitor), LY23200882 (TGF-β/Smad inhibitor) and PD98059 (MAPK/ERK inhibitor). Western blot analysis over 7, 14, and 21 days and LC-MS/MS proteomic profiling on day 21 revealed that the PI3K/AKT signalling pathway is crucial for the osteogenic differentiation of DPSC on both OIM and Col-1 group. PI3K/AKT pathway was predominant throughout the 21 days of Col-1 induced osteogenesis, while MAPK/ERK and TGF-β/Smad was more relevant at earlier and later stage, respectively. Crosstalk between signalling molecules showed bidirectional or unidirectional dependent to each other, where AKT activation can be influenced by Smad, but not vice versa. Likewise, Smad activation can be influenced by ERK1/2, but not the other way around. Proteomic profiling of Col-1 induced osteogenesis showed majority of the proteins were associated with glycolysis, carbon metabolism, biosynthesis of amino acid and focal adhesion.